Penerapan Metode Waterfall Pada Aplikasi Reservasi Lapangan Futsal Berbasis Web - Temi Ardiansah; Dani Hidayatullah (PT. Tech Cart Press, 2023)
This study aims to make it easier to provide scheduling information, the leasing process, and making financial reports. The benefits of this research can find out booking transactions, financial reports, scheduling information, and services at the Bandar Lampung Sport Center. For data collection methods using several methods such as observation, interviews, and literature studies. While the method for developing the system uses the waterfall method. The results of this study are in the form of a web-based application that can make it easier for customers and managers. The results of the tests carried out using the Black Box method with a valid category with a result of 100%, then this test can be said to be successful,, it is concluded that the applications that have been made can run well.